Klasifikasi Data Aktivitas Setelah Joging Menggunakan Fuzzy Logic - M. Deta Gian Faiz; Andrian Rakhmatsyah; Rahmat Yasirandi (Ikatan Ahli Informatika Indonesia (IAII), 2021)
One of the routine activities that cause a lot of body fluids is jogging. Research shows that excessive jogging can disrupt the balance of body fluids so that you tire quickly in the long run. As a result, the body releases too much fluid. This makes someone forget or underestimate the need for fluids in the body. In this study, a detection system for body temperature, ambient temperature and heart rate was built for the classification of dehydration in the body to maintain fluid stability in the body. The system is built using the Pulse Sensor, Mlx90614, OpenWeatherAPI and the Android Platform. This study uses the Mamdani Fuzzy Logic method to determine the classification of user dehydration. The results of the research analysis contained a calibration test of the MLX90614 sensor against the Thermogun with an Error Rate value of 2.01% and an RMSE value of 0.9. Testing the Pulse Sensor against the Oximeter produces an Error Rate value of 1.54% and an RMSE value of 0.7. There is a difference in the difference in Deffuzification values ​​due to differences in the fixed points for each library. Matlab fixed point with a value behind the three digit point, 16 digit Fuzzy Sci-kit and the Builded System using a 15 digit point value.